Anti-phishing model for phishing websites detection: using pruning decision tree [electronic resource] - Ahmed I. M. Abunadi, 1986- (2013)
Thesis (Sarjana Sains Komputer (Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2013